2020
DOI: 10.3390/nu13010060
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Whole Blood Cu and Zn Status in Predicting Mortality in Lung Cancer Patients

Abstract: Alterations in circulating Cu and Zn are negative predictors of survival in neoplastic patients and are known during lung cancer. However, no data on predicting mortality of lung cancer patients based on the level of these elements in the blood have been presented to date. The aims of this prospective cohort study were as follows: (i) To evaluate the disturbances in serum and whole blood Cu and Zn, (ii) to assess the relationships between serum and whole blood Cu and Zn status and clinical, sociodemographic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 68 publications
(86 reference statements)
2
34
0
Order By: Relevance
“…Similar to Cu levels, the ratio of serum Cu/Zn levels was also significantly higher in cancer patients compared to healthy controls, which typically resulted from the increase of Cu levels with simultaneous decrease of Zn levels. Recently, several studies aimed to determine whether circulating Cu levels in serum and full blood, and the ratio of Cu/Zn levels can serve as predictors of the patients’ mortality [ 32 , 33 , 34 , 35 ]. It was demonstrated that higher serum Cu levels, as well as Cu/Zn ratio, were associated with increased all-cause mortality in lung cancer patients [ 32 ].…”
Section: Systemic Changes In Cu Homeostasis Of Cancer Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to Cu levels, the ratio of serum Cu/Zn levels was also significantly higher in cancer patients compared to healthy controls, which typically resulted from the increase of Cu levels with simultaneous decrease of Zn levels. Recently, several studies aimed to determine whether circulating Cu levels in serum and full blood, and the ratio of Cu/Zn levels can serve as predictors of the patients’ mortality [ 32 , 33 , 34 , 35 ]. It was demonstrated that higher serum Cu levels, as well as Cu/Zn ratio, were associated with increased all-cause mortality in lung cancer patients [ 32 ].…”
Section: Systemic Changes In Cu Homeostasis Of Cancer Patientsmentioning
confidence: 99%
“…Recently, several studies aimed to determine whether circulating Cu levels in serum and full blood, and the ratio of Cu/Zn levels can serve as predictors of the patients’ mortality [ 32 , 33 , 34 , 35 ]. It was demonstrated that higher serum Cu levels, as well as Cu/Zn ratio, were associated with increased all-cause mortality in lung cancer patients [ 32 ]. This might be associated with the increase of Cu levels and Cu/Zn ratio at advanced stages of the disease, as well as during metastatic progression, thus resulting in lowered survivability [ 32 , 33 , 34 , 35 ].…”
Section: Systemic Changes In Cu Homeostasis Of Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that an elevated fraction of free cooper in serum may be harmful due to its significant oxidation–reduction potential through the generation of reactive oxygen species in Fenton and Haber–Weiss type reactions [ 21 ]. They are essential to the operating of the immune system and proper functioning of a variety of physiological and biochemical processes [ 22 , 23 ]. Apart from being a cofactor for numerous enzymes, they play the key role in the development and functioning of the central nervous system [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…567 Changes in systemic levels of transition metals occur during carcinogenesis and vary according to the type of cancer, metal ion, and other biological factors. [568][569][570][571][572][573][574][575] Proliferating cancer cells have a higher demand for Cu than normal cells, 576 so limiting Cu availability during carcinogenesis might be a way to slow cancer progression. 577 Conversely, high levels of Cu can inhibit cell proliferation and tumor growth.…”
Section: Roles As a Promoter And An Inhibitor Of Cancermentioning
confidence: 99%